THE IMPLICATION OF WINDING UP DEVELOPERS ON STRATA OWNERSHIP IN MALAYSIA: A CRITICAL REVIEW - Hishamuddin, Helmi Hariri; Mohsin, Aminah (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
The process of obtaining strata titles in Malaysia involves four procedural stages, yet many purchasers remain without formal ownership, as their properties are still held under master titles. As of June 2020, over 440,000 parcels across 1,528 schemes in Peninsular Malaysia had not been issued individual strata titles. This issue is compounded when developers undergo winding-up proceedings, leaving purchasers in a legally uncertain position. With 296 recorded cases of developer insolvency since 1984, the implications for strata ownership are significant. This critical review examines the legal, financial, and administrative consequences of winding-up developers on strata title issuance. Using a systematic analysis of statutory provisions, regulatory frameworks, and existing literature, the study identifies five key implications: increased financial burden on purchasers, restrictions on property transactions, weakened management structures, unsecured creditor status, and inheritance complications. To address these challenges, the study recommends legislative reforms, including the establishment of dedicated guarantee funds, implementation of project account systems, and enhanced regulatory oversight. These measures aim to protect purchasers’ rights and ensure the continuity of strata title administration, even in cases of developer insolvency.